Sustainable garden : projects, tips and advice for the eco-conscious gardener - Boswall, Marian (Frances Lincoln, 2022)
A stylish, inspirational and practical guidebook to maintaining a more environmentally friendly outdoor space. Sustainable gardener Marian Boswell walks us through the process of creating and maintaining a sustainable outdoor space, offering tips, guidances and step-by-step projects designed to help you lead a more low-impact lifestyle. Whether it's by making your own fertilisers, converting to peat-free compost, reducing your consumption of plastic, saving your own seeds or creating raised beds with reused timber, there are numerous ways - both big and small - to make a difference. This book will guide anyone hoping to take informed and intelligent decisions to make a difference, but who perhaps don't know where to begin.